Development of the ICF-CY Set for Cardiac Rehabilitation After Pediatric Congenital Heart Surgery - Luo, Wen-Yi; Ni, Ping; Chen, Lin; Pan, Qian-Qian; Zhang, Hao; Zhang, Ya-Qing (Frontiers in Pediatrics, 2022)
Background: Most children with congenital heart disease (CHD) require surgical repair and postoperative rehabilitation is an essential step to restore the quality of life. The present study aimed to construct and confirm the International Classification of Functioning, Disability, and Health for Children and Youth core set in children with congenital heart disease after surgery (ICF-CY-CHDS). Methods: From February 2021 to August 2021, 340 children aged 3 ~ 6 years after CHD surgery were evaluated by ICF-CY-CHDS, and analyzed by the Rasch model. Results: The finial ICF-CY-CHDS contained 22 categories. It exhibited a nonsignificant test result for the item-trait interaction (X2=6736.37, p=0.8660, Bonferroni-adjusted p=0.05/22=0.0023). The average value of severity children is less than the average difficulty of categories (-2.26 logit > 0 logit). The weighted k of over all categories was 0.964 (p<0.001) and the item separation index was 0.96. The area under the ROC curve with the diagnosis result of heart failure in children is 0.866 (95% CI: 0.801 ~ 0.931) with good sensitivity (0.875) and specificity (0.759). Conclusion: The ICF-CY-CHDS presents preliminary practice content during cardiac rehabilitation after pediatric CHD surgery, which provided a basis and scope for clinical evaluation and intervention program formulation.